Tying the CNOT: CNOT1 regulates poly(A) tail length at the end and the beginning - Williams, Kathryn (2021)
Poly(A) tails affect multiple aspects of gene regulation: they help identify mRNAs for nuclear export, enhance translation efficiency, and are essential to regulating mRNA degradation rate. A poly(A) tail of 200-250 residues is thought to be uniformly added to newly synthesised mRNA and later gradually removed in the cytoplasm, allowing degradation of the mRNA itself.